Large-eddy simulations of gravity currents in the presence of waves. Issue 5 (3rd September 2022) - Cui, Ting; Kamath, Arun; Wang, Weizhi; Han, Duanfeng; Bihs, Hans
Abstract : Simulations are performed to investigate gravity currents in the presence of free surface waves using the open-source computational fluid dynamics programme REEF3D with the concentration equation, and the large eddy simulation model for turbulence closure. Simulations show that the period of the oscillation front relates only to the period of the incident waves and the oscillation amplitude increases with wave height. The average velocity of the density current increases with increasing wave height and wavelength. The surface waves change the generation position and combination direction of the turbulence structures in the pycnocline. The oscillatory motion of the waves stabilizes the pycnocline earlier and reduces the turbulent mixing. The instability zone is reduced faster with higher wave heights with well-ordered K-H billows, but not for longer wavelengths. The instantaneous velocity and concentration fields are highly influenced by the incident wave characteristics when compared to that in the absence of waves.